Anxiety increases visual attention to hedonic foods: A preliminary eye-tracking study on the impact of the interplay between integral and incidental affect on foods. (1st June 2019) - Motoki, Kosuke; Saito, Toshiki; Nouchi, Rui; Kawashima, Ryuta; Sugiura, Motoaki
Abstract: Two types of affect influence consumers' attention: incidental affect unrelated to a particular perception or judgment and integral affect directly related to the particular options under consideration. Although integral and incidental affect likely coexist on a regular basis, the claim that both concurrently guide consumers' attention has thus far received little attention. To fill this gap, the present study investigated the effects of the interplay of integral and incidental affect on the visual processing of food. Food labels play an essential role in attracting consumer attention. Food labels include sources of integral affect (e.g., food type, pictures), and consumers often view food labels under the influence of incidental affect (e.g., an unrelated anxiety-inducing message or personal experience). According to the appraisal tendency framework, incidental experiences of anxiety can enhance affective processing of food due to the uncertainty associated with anxiety. In our study, participants were first subjected to manipulation of an incidental emotion (anxiety, anger, or neutral). Then, they passively viewed food labels, including pictures and nutrient labels, for hedonic and healthy foods. Subject's eye movements were tracked during this stage of the study. Our results showed that the induction of incidental anxiety, but not anger or neutral feelings, led to greater visual attention on hedonic foods only. These findings shed light on the interplay between incidental and integral affect in consumer information processing, demonstrating that the co-occurrence of incidental anxiety and integral hedonic feelings enhance visual attention to food.